2006
DOI: 10.4103/0019-5545.31602
|View full text |Cite
|
Sign up to set email alerts
|

Psychological assessment of alcoholism in males

Abstract: Background:Little work has been done in India on the personality factors of alcoholics. These personality factors have a significant effect on treatment outcome.Aim:To study the personality characteristics, stressful life events and diagnostic utility of the Michigan Alcoholism Screening Test (MAST) and CAGE (Cutting down, Annoyance by criticism, Guilty feeling, and Eye-opener) Questionnaire in service personnel with alcohol dependence.Methods:Psychological assessment of 100 consecutive male inpatients meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 10 publications
5
29
0
Order By: Relevance
“…In our study the mean age of the tharraconsumers was around 32±5, similar to studies by Butt and Chaudhary [24,32] who reported range between 30±40 and 31±5 years respectively in contrast to our findings. A study in Pakistan reported the mean age ranges between 25±5 years.…”
Section: Socioeconomic and Health Determinants Of Liquor Consumerssupporting
confidence: 88%
See 2 more Smart Citations
“…In our study the mean age of the tharraconsumers was around 32±5, similar to studies by Butt and Chaudhary [24,32] who reported range between 30±40 and 31±5 years respectively in contrast to our findings. A study in Pakistan reported the mean age ranges between 25±5 years.…”
Section: Socioeconomic and Health Determinants Of Liquor Consumerssupporting
confidence: 88%
“…Our study further explored that, most of the liquor consumers, drink tharra on daily basis (37.7%) as compared to a similar kind of study in other province of Pakistan named Punjab and in Nepal [32][33] showed similar trends of 40% and 38% respectively, however our findings vary from the studies conducted in India and Tanzania where the homemade liquor consumption was reported as 48and 14.7-47 % respectively [33][34].…”
Section: Socioeconomic and Health Determinants Of Liquor Consumersmentioning
confidence: 55%
See 1 more Smart Citation
“…Depression was reported in 78% of the study population. Chaudhary & DAS[15] reported significant depression and anxious disorders in their alcoholic sample. Forty-two were suffering from anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Hence for successful treatment and management of alcohol dependent cases, it is essential to understand their personality. 1 Some believe that alcoholism and anxiety disorders go hand in hand. They exist as co-morbidity.…”
Section: Introductionmentioning
confidence: 99%